2021
DOI: 10.9770/jesi.2021.8.3(8)
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cooperatives in Italy

Abstract: The purpose of this contribution is to photograph and describe, with reasonable accuracy and beginning from the territorial, time and sectoral distribution, the Italian cooperative universe in all its main economic, size and qualitative variables. In the light of the economic crisis triggered by the present epidemic, the mapping work also takes on a further importance in outlining a perspective of analyses on the future impacts of the recession, on the resilience of the cooperative movement and on the role it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Similarly, it was thanks to Christian priests that the cooperative idea was disseminated. At times, when politics or religion were not involved, it was the owner of the firm itself who would recommend workers adopt a form of collective ownership; this was the case with John Lewis and many Italian firms that were donated to the workers on the condition that they would organise them in the form of a co-operative [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was thanks to Christian priests that the cooperative idea was disseminated. At times, when politics or religion were not involved, it was the owner of the firm itself who would recommend workers adopt a form of collective ownership; this was the case with John Lewis and many Italian firms that were donated to the workers on the condition that they would organise them in the form of a co-operative [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, co-operative firms spread and developed with the support of radical initiatives and an adequate institutional environment. Co-operatives have been flourishing the most in areas where they were supported by a socalled 'enabling environment', involving appropriate legislation, co-operative associations, targeted funding opportunities from members, co-operative banks and local, national and supranational institutions [10].…”
Section: Introductionmentioning
confidence: 99%
“…4 See, for instance, Zamagni and Zamagni (2011) for a thoughtful account of the Italian cooperative movement. To grasp an order of magnitude of the economic presence of cooperative companies worldwide, see ICA (2017); for the Italian economy, see Borzaga et al (2019), Istat (2019) and Cori et al (2021). According to Istat (2019), in 2015, including subsidiaries, the cooperative companies account for about 1,215,000 employees (7.4% of total employment in the Italian private sector) and over 32 billion euros (4.4% of the corresponding added value) This countercyclical behaviour then protects employment and sustains labour incomes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Amorato (2017),Borzaga et al (2019),Istat (2019),Cori et al (2021), OECD (2021. For an exhaustive historical account of the problems faced by the cooperative form, and some policy directions, seeDow (2018).26 InCosta et al (2021) it is shown that in Italy the size of cooperative employment is positively associated to an index of regional prosperity which considers both household's disposable income and its distribution across households.27 Incidentally, a special attention to cooperatives in Italy is established in art.…”
mentioning
confidence: 99%
“…Similarly, it was thanks to Cristian priests that the cooperative idea was disseminated. At times, when politics or religion were not involved, it was the owner of the firm itself to recommend workers to adopt a form of collective ownership; this was the case of John Lewis and many Italian firms that were donated to the workers on the condition of organizing them in the form of a cooperative (Paranque and Willmott, 2016;Cori et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%